Drug-drug Interaction Management in Internal Medicine Specialty - Abu-Elsoud, Nermeen Nabeel (Asian Journal of Pharmaceutics (AJP), 2017)
Aim: Many studies were conducted to ensure the role of clinical pharmacists in medication management and patient safety. However, there are no studies focused on drug interaction (DI) management in the Middle East hospitals. Objectives: The objectives of this study were to determine DI types, classify them according to their clinical significance, study their effect on the clinical outcomes, and raise recommendations about their management. Materials and Methods: Study Design - This prospective evaluation with descriptive analysis study conducted on 89 patients in the internal medicine department of a tertiary care hospital. Each DI was assessed using Lexicomp and Medscape DI databases, and based on its severity and its expected effect on the efficacy or toxicity of the treatment plan, certain interventions were provided to manage these DIs. The interventions included discontinuation of certain medications in case of severe interactions, monitoring of specific laboratory parameter such as international normalized ratio, potassium or digoxin serum levels, or changing certain drugs to another non-interacting one. Results: A total of 191 DIs were detected, 54.5% of them may increase the treatments’ toxicities, and 45.5 % may decrease the treatment efficacy. Among the detected DIs, 33% required stopping one of the two drugs. About 29% of DIs required monitoring drug serum level or pharmacological effect. Pharmacokinetic interaction rate represented 67%. Conclusion: The results of this study emphasize the active role of clinical pharmacists in detecting and managing different types of DIs in internal medicine specialty. This is the first study that focuses on managing the DIs based on the patients’ conditions.